Role of Immunochromatographic Test for Rapid diagnosis of Malaria - Ahmed, MU; Mahmud, MC; Shamsuzzaman, AK; Musa, AK; Ahmed, SU; Alam, M; Khan, AH; Kabir, MU; Sumona, AA; Ahmed, S; Haque, N; Hossain, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):106-109. The abstract of this article is available on the PubMed website